Celastrol: A Spectrum of Treatment Opportunities in Chronic Diseases - Cascão, Rita; Fonseca, João E.; Moita, Luis F. (Frontiers in Medicine, 2017)
Abstract The identification of new bioactive compounds derived from medicinal plants with significant therapeutic properties has attracted considerable interest in recent years. Such is the case of the Tripterygium wilfordii, an herb used in Chinese medicine. Clinical trials performed so far using its root extracts have shown impressive therapeutic properties, but also revealed substantial gastrointestinal side-effects. The most promising bioactive compound obtained from Tripterygium wilfordii is celastrol. During the last decade, an increasing number of studies were published highlighting the medicinal usefulness of celastrol in diverse clinical areas. Here we systematically review the mechanism of action and the therapeutic properties of celastrol in inflammatory diseases, namely rheumatoid arthritis, systemic lupus erythematosus, inflammatory bowel diseases, osteoarthritis and allergy, as well as in cancer, neurodegenerative disorders and other diseases, such as diabetes, obesity, atherosclerosis and hearing loss. We will also focus in the toxicological profile and limitations of celastrol formulation, namely solubility, bioavailability and dosage issues that still limit its further clinical application and usefulness.